2017
DOI: 10.1152/ajplung.00188.2016
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 blocks myofibroblast differentiation and pulmonary fibrosis by preventing mitochondrial DNA damage

Abstract: Myofibroblast differentiation is a key process in the pathogenesis of fibrotic diseases. Transforming growth factor-β (TGF-β) is a powerful inducer of myofibroblast differentiation and is implicated in pathogenesis of tissue fibrosis. This study was undertaken to determine the role of mitochondrial deacetylase SIRT3 in TGF-β-induced myofibroblast differentiation in vitro and lung fibrosis in vivo. Treatment of human lung fibroblasts with TGF-β resulted in increased expression of fibrosis markers, smooth muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 60 publications
7
67
0
Order By: Relevance
“…Interestingly, OGG1 levels are reduced in SIRT3-deficient mice with a consequent increase in 8-Oxo-dG levels and mtDNA damage. Consistent with these data, mice overexpressing SIRT3 have sustained expression of OGG1, preserved mtDNA integrity and are protected from bleomycin-induced lung fibrosis 203 . As a therapeutic approach, mitochondria-targeted OGG1 has been shown to limit oxidant-induced mtDNA damage and lung injury 205,206 .…”
Section: Targets and Therapeutic Interventions For Mitochondrial Damagesupporting
confidence: 67%
See 1 more Smart Citation
“…Interestingly, OGG1 levels are reduced in SIRT3-deficient mice with a consequent increase in 8-Oxo-dG levels and mtDNA damage. Consistent with these data, mice overexpressing SIRT3 have sustained expression of OGG1, preserved mtDNA integrity and are protected from bleomycin-induced lung fibrosis 203 . As a therapeutic approach, mitochondria-targeted OGG1 has been shown to limit oxidant-induced mtDNA damage and lung injury 205,206 .…”
Section: Targets and Therapeutic Interventions For Mitochondrial Damagesupporting
confidence: 67%
“…SIRT3 expression decreases with age, and mice deficient in SIRT3 develop spontaneous tissue fibrosis in multiple organs, including the lungs, with age 199,200 . SIRT3 expression is diminished in the skin and lungs of patients with systemic sclerosis 201 , and mice deficient in SIRT3 are more susceptible than wild-type mice to bleomycin-induced lung fibrosis 202,203 . Two main mechanisms have been described as potential SIRT3-mediated protective mechanisms against fibrosis.…”
Section: Targets and Therapeutic Interventions For Mitochondrial Damagementioning
confidence: 99%
“…Other studies showed similar fibrosis-inhibiting effects mediated by SIRT1 in cultured fibroblasts from patients with hypertrophic scars [103] and transformed human and mouse fibroblast cell lines [99]. Similar to studies on SIRT1, several groups found that SIRT3 inhibited TGF-β-induced profibrotic effects such as increases in collagen, alpha-smooth muscle actin (α-SMA), or plasminogen activator inhibitor-1 (PAI1) in cultured normal human lung or skin fibroblasts [111113]. Similar effects were seen in vivo with exaggerated profibrotic responses to bleomycin in SIRT3 KO mice [112114] and decreased bleomycin-induced lung fibrosis in SIRT3 transgenic mice [113].…”
Section: Sirtuins and Sclerodermamentioning
confidence: 90%
“…Similar to studies on SIRT1, several groups found that SIRT3 inhibited TGF-β-induced profibrotic effects such as increases in collagen, alpha-smooth muscle actin (α-SMA), or plasminogen activator inhibitor-1 (PAI1) in cultured normal human lung or skin fibroblasts [111113]. Similar effects were seen in vivo with exaggerated profibrotic responses to bleomycin in SIRT3 KO mice [112114] and decreased bleomycin-induced lung fibrosis in SIRT3 transgenic mice [113]. Intratracheal adenoviral delivery of SIRT6 similarly suppressed bleomycin-induced epithelial to mesenchymal transition (EMT) in murine lung [119].…”
Section: Sirtuins and Sclerodermamentioning
confidence: 99%
See 1 more Smart Citation